English language teaching now and how it could be - Jordan, Geoff (Cambridge Scholars Publishing, 2022)
This book argues that, to teach languages well, one needs to know how people learn them, and that current English Language teaching (ELT) practice largely ignores this vital question. It offers an up-to-date, accessible discussion of recent developments in knowledge about second and foreign language learning, as well as implications for language teaching. It then provides a critical analysis of the current ELT industry, arguing that its increasing commercialization has led to poor teaching, dull materials, inadequate second language teaching education, and testing procedures that are unfit for.